Massive pleural effusion due to paragonimiasis: Biochemical, cytological, and parasitological findings - Takhellambam Shantikumar Singh; Hiromu Sugiyama; Chultin Lepcha; Satish Kumar Khanna (Wolters Kluwer Medknow Publications, 2014)
Paragonimiasis is an important food-borne parasitic zoonosis caused by trematode species of the genus, Paragonimus occurring in many parts of the world except in Australia and Antarctica. In India, it is an emerging parasitic disease, which is endemic in the northeast states where people have a common practice of eating raw or inadequately cooked freshwater crabs. In these states, Paragonimus heterotremus has been identified as the major causative agent of the human paragonimiasis. The most common clinical form of the disease is pulmonary paragonimiasis; however, extra-pulmonary manifestations are not uncommon. Here, we report a case of primary massive unilateral pleural effusion due to paragonimiasis. The diagnosis was confirmed by finding Paragonimus ova in the pleural fluid. The patient was successfully treated with repeated thoracocentesis and a course of praziquantel.